Structure, Performance, and Application of BiFeO3 Nanomaterials - Wang, Nan; Luo, Xudong; Han, Lu; Zhang, Zhiqiang; Zhang, Renyun; Olin, Håkan; Yang, Ya (Nano-Micro Letters, 2020)
Multiferroic nanomaterials have attracted great interest due to simultaneous two or more properties such as ferroelectricity, ferromagnetism, and ferroelasticity, which can promise a broad application in multifunctional, low-power consumption, environmentally friendly devices. Bismuth ferrite (BiFeO3, BFO) exhibits both (anti)ferromagnetic and ferroelectric properties at room temperature. Thus, it has played an increasingly important role in multiferroic system. In this review, we systematically discussed the developments of BFO nanomaterials including morphology, structures, properties, and potential applications in multiferroic devices with novel functions. Even the opportunities and challenges were all analyzed and summarized. We hope this review can act as an updating and encourage more researchers to push on the development of BFO nanomaterials in the future. Highlights: 1 The development of bismuth ferrite as a multiferroic nanomaterial is summarized. 2 The morphology, structures, and properties of bismuth ferrite and its potential applications in multiferroic devices with novel functions are presented and discussed. 3 Some perspectives and issues needed to be solved are described.